Italian military operations abroad just don't call it war - Ignazi, Piero (Palgrave Macmillan, 2012)
Peace support operations are one of the most important tools in the foreign policy of Western democracies. This book is a study of Italian military operations in the last twenty years. Italy's operations are examined through an analysis of parliamentary debates and interviews with leading policy-makers.